2001
DOI: 10.1097/00000539-200110000-00050
|View full text |Cite
|
Sign up to set email alerts
|

The Continuous Femoral Nerve Block Catheter for Postoperative Analgesia: Bacterial Colonization, Infectious Rate and Adverse Effects

Abstract: In this prospective study, continuous femoral nerve catheters were effective for postoperative analgesia but had a frequent rate of bacterial catheter colonization. We found no serious infections after short-term (2-day) infusion. Side effects were few, but one nerve injury occurred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
1
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(157 citation statements)
references
References 11 publications
6
141
1
9
Order By: Relevance
“…Although we did not observe permanent nerve damage in the patients in the femoral nerve block group, the rates in two series ranged from 0.1% to 0.4% [10,24]. Even if our study was not adequately powered (210 patients were needed) to compare DVT rates, earlier and improved mobilization with PAI may reduce venous stasis and thrombosis.…”
Section: Discussionmentioning
confidence: 63%
“…Although we did not observe permanent nerve damage in the patients in the femoral nerve block group, the rates in two series ranged from 0.1% to 0.4% [10,24]. Even if our study was not adequately powered (210 patients were needed) to compare DVT rates, earlier and improved mobilization with PAI may reduce venous stasis and thrombosis.…”
Section: Discussionmentioning
confidence: 63%
“…Fortunately, the reported incidence of local inflammatory signs was only 3%. Cuvillon et al 27 prospectively reported an incidence of 57% of colonized femoral catheters and only 1.5% of bacteremia. Similarly, the risk of epidural infection is low in the pediatric population undergoing short-term perioperative treatment.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…However, this requires placement of a perineural catheter, 11,12 continuous infusion of local anesthetic, inconvenience of carrying catheter and local anesthetic reservoir/pump, infusion management and catheter site care, infection, leakage, accidental dislocation, and cost and maintenance of equipment. 11,13 Liposome bupivacaine (bupivacaine liposome injectable suspension; EXPAREL ® ; Pacira Pharmaceuticals, Inc., USA) is a multivesicular formulation of bupivacaine indicated for administration into the surgical site to produce postsurgical analgesia. 14 Liposome bupivacaine has been shown to provide postsurgical analgesia across a range of surgical models, with a safety profile that is similar to that of bupivacaine HCl.…”
mentioning
confidence: 99%